Energy Transfer Medicine Practiced by Shamans in Kelurahan Sungai Bangkong, Pontianak City District - Nurhasanah Nurhasanah; Arkanudin Arkanudin; Viza Juliansyah (Universitas Tanjungpura, 2022)
Traditional medicine still exists and is still believed by some people. One of the traditional treatment methods is the energy transfer treatment method which is practiced in the Kelurahan Sungai Bangkong area, Pontianak City District, Pontianak City. The main focus of this research problem is how this treatment still survives today, what is its history, and what are the meanings in energy transfer medicine practiced by Shaman. This study further explores how these practitioners interpret unconventional energy transfer treatment as a way to cure their patients' ailments. Qualitative method is the method used in this research and data were collected through interviews and observations. The results of this study describe what can be found in the field data and explain how the practice of energy transfer treatment is practiced.